Brexit a drama: the endgame - Part I - Craig, P (Sweet and Maxwell, 2020)
This, the first article in a series, analyses the processes culminating in the UK's departure from the EU. Reviews key provisions of the first Withdrawal Agreement of November 2018, including the Political Declaration and Northern Ireland backstop, and examines the negotiating strategies of the UK and EU executives, and the response of the UK legislature. Discusses the revisions made to the initial text of the agreement, and considers the impending challenges for the UK Government.